Metamorfoses do trabalho: a precarização do trabalho plataformizado e a (des) regulamentação na cidade de Manaus - Pinheiro, Monique Alves (Brasil, 2025)
This research investigates the precarization of platform-mediated work and its (de)regulation in Manaus, aiming to understand the connections between the process of precarization and the local legislative production that impacts the rights of workers in this sector. To this end, an inventory of local legislative initiatives is conducted, with the objective of assessing their impact on the consolidation of social rights for these workers. The study adopts a qualitative approach, based on bibliographic and documentary analyses, mapping the bills (PLs) from